Empowering Communities for Islamic Eco-Friendly House Development: A Case Study in a Tourist Village - Rihlah Nur Aulia; Faisal M. Jasin; Sugeng Priyanto; Muhamad Ridwan Effendi; Ismayati Afifah (Universitas Muhammadiyah Sidoarjo, 2023)
This study focuses on enhancing community engagement in fostering environmentally sustainable practices through the implementation of eco-friendly housing in Cisaat Village. By harnessing the potential of nature and adopting a sustainable lifestyle, the concept of eco-friendly houses contributes to mitigating environmental damage and addressing climate change. Using an Islamic environmental approach, this research aimed to strengthen the role of the Cisaat Muslim community in promoting eco-friendly houses as exemplars of sustainable living. The service design encompassed five stages: observation, preparation, implementation, assistance, and evaluation. Results indicated a substantial positive impact, with 98% of participants acknowledging the utility of the provided material and 95% expressing high satisfaction with the conducted activities. The implication of this study lies in the heightened knowledge and competence within the community regarding eco-friendly house development, signifying a significant step toward realizing environmentally conscious homes in the educational tourism village of Cisaat. Highlight: Eco-friendly Housing for Sustainability: This study emphasizes the role of eco-friendly housing in mitigating environmental damage and addressing climate change by integrating nature's potential and sustainable living practices. Islamic Environmental Approach: The research focuses on enhancing the Cisaat Muslim community's involvement in advocating eco-friendly housing, aligning with an Islamic environmental approach. Effective Service Design: Employing a comprehensive service design with five stages ensures the successful implementation of community engagement, resulting in a significant positive impact, as evidenced by high participant satisfaction and increased knowledge about eco-friendly house development. Keyword: Community Engagement, Eco-Friendly Housing, Islamic Environmental Approach, Sustainable Living, Environmental Awareness